A Guide to Understanding the Fundamental Principles of Environmental Management It Ain't Magic: Everything Goes Somewhere - Manale, Andy (IWA Publishing, 2021)
In this human-dominated "Anthropocene Epoch," how does one protect and manage scarce environmental resources? This book uses plain language to introduce the non-expert to the fundamentals of environmental management, without requiring them to have a solid grounding in the basic sciences. The authors build upon the reader's natural understanding of scientific principles to learn how to follow the consequences of change through natural systems and to ask better questions about one's environment. Case studies are provided, drawn from temperate ecosystems and human-altered landscapes. Two sets of stories are crafted to explain scientific concepts and introduce analytical approaches, identifying where and how to obtain relevant information. The first covers water and where it goes and what factors affect its fate, and the second how key building blocks of life (carbon and the nutrients, nitrogen and phosphorus) change chemical forms and cycles through the environment. The role of soils in the nexus of environmental media is explained. Finally, the authors describe, and also lead the reader to identify, how humans have altered core processes and to judge the significance of these changes. The reader will learn how to fix environmental dysfunction in both private and public lives.